Women in peace politics - Banerjee, Paula (South Asian peace studies ;, 2008)
Women in Peace Politics explores the role of women as agents and visionaries. of peace in South Asia. Peace is redefined to include in its fold the attempt. by women to be a part of the peace making process, reworking the structural inequalities. faced by them and their struggle against all forms of oppression. This volume, the third in the series of the South Asia Peace Studies, deals. with the myriad dimensions of peace as practised by South Asian women over a. period of time. It chronicles the lives of "ordinary" womentheir. transformative role in peace and an attempt to create a.